The Character Development of the Minor Character Neville Longbottom in Harry Potter Series - , ALVANITA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This graduating paper examines novel series entitled Harry Potter written by J.K. Rowling. There are seven series telling about the journey of Harry Potter in Hogwarts, a school of witchcraft and wizardry. The objectives of this paper are to study the character development of Neville Longbottom, one minor character in Harry Potter and to find his significance in the Harry Potter series. The analysis is conducted with objective approach. Objective approach is chosen to analyze the plot, character, and characterization. Therefore, it can fully examine the changes of Neville character. The result of this research shows that Neville character is changed significantly during the series. Moreover, his development becomes very significant to the plot of Harry Potter. At first, he is obedient and shy, but finally in the end of the series he becomes a hero. He is a minor character, yet he plays significant role.